Respuesta :
[tex]\longrightarrow{\green{59}}[/tex]
[tex]\large\mathfrak{{\pmb{\underline{\red{Step-by-step\:explanation}}{\red{:}}}}}[/tex]
[tex]53 + 3(5 - 3) \\ \\ = 53 + 3(2) \\ \\ = 53 + 6 \\ \\ = 59[/tex]
Note:-
[tex]\sf\purple{PEMDAS\: rule.}[/tex]
P = Parentheses
E = Exponents
M = Multiplication
D = Division
A = Addition
S = Subtraction
[tex]\bold{ \green{ \star{ \orange{Mystique35}}}}⋆[/tex]
[tex]\mathrm{Follow\:the\:PEMDAS\:order\:of\:operations}[/tex]
Calculate within parenthesis
[tex]5-3\\\\=2[/tex]
[tex]=53+3\cdot \:2[/tex]
Multiply and divide
[tex]3\cdot \:2\\\\=6[/tex]
[tex]=53+6[/tex]
Add and subtract
[tex]53+6\\\\= 59[/tex]
So, the simplified expression of [tex]53 + 3(5 - 3)[/tex] is 59